1996
DOI: 10.1111/j.1523-536x.1996.tb00835.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Topical Agents to Relieve Nipple Pain and Enhance Breastfeeding

Abstract: Further investigation is required into ways of supporting young mothers and how caregivers provide support to breastfeeding mothers in the early weeks after childbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 17 publications
0
46
0
1
Order By: Relevance
“…The beneficial effects of lanolin in the prevention or treatment of sore or damaged nipples have been demonstrated before [1,8,38] . However, in these trials lanolin has always been compared to or combined with other interventions, and the purity, quality and form of the lanolin and the frequency of application have varied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of lanolin in the prevention or treatment of sore or damaged nipples have been demonstrated before [1,8,38] . However, in these trials lanolin has always been compared to or combined with other interventions, and the purity, quality and form of the lanolin and the frequency of application have varied.…”
Section: Discussionmentioning
confidence: 99%
“…ing education [1,3,[6][7][8] . However, there is little evidence from prospective trials regarding the use of topical agents [9][10][11][12][13] .…”
mentioning
confidence: 99%
“…In all cases, there was minimal blood loss, that is, no more than a drop or two, collected on sterile gauze, and infant crying lasted a few seconds only. In every sequence, and after each sham or frenotomy procedure, a standardized latch score [9] (10 points minimum difficulties) and pain score using a standard visual analogue pain scale [10] (10 points maximum pain) were obtained from the mother by the lactation consultant.…”
Section: Methodsmentioning
confidence: 99%
“…The conclusion was that no difference exists between the different treatments with regard to pain intensity and maintenance of breastfeeding. 11 Another study revealed that modified lanolin is useful in alleviating nipple pain, especially between the sixth and tenth days after delivery. 12 A practice that has become quite popular in some Brazilian regions is the use of tea bags for the treatment of sore nipple.…”
Section: Treatmentmentioning
confidence: 99%